HUBUNGAN PERILAKU DAN KONDISI FISIK RUMAH DENGAN KEKAMBUHAN MALARIA DI WILAYAH KERJA PUSKESMAS SUNGAI ABANG KABUPATEN TEBO - Delfan Mardani; Salvita Fitrianti; Yunita Rahmadhani (Jurnal Akademika Baiturrahim Jambi, 2016)
Backround: The problem of malaria is becoming increasingly difficult to overcome and is expected to be an obstacle to successful health development. Malaria re-attacks are related to the existence of malaria vector namely environmental condition, physical condition of house and human that is immunity, drug resistance and behavior (night habit at night, habit of wearing mosquito net, habit of using mosquito repellent). This study aims to determine the relationship between behavior and physical condition of the house with malaria recurrence in the Work Area Puskesmas Sungai Abang District VII koto Tebo DistrictMethod: This research is a quantitative cross sectional design. The study was conducted in September 2015 with a sample size of 30 respondents. Data were obtained using questionnaire, univariate and bivariate analyzed, looking for correlation using chi-square test.The result: of the research analysis is known from 30 respondents, it is known 56,7% of respondents happened malaria recurrence, 70% of respondents have good behavior, 83,3% of respondent have physical condition of house at high risk. The result of statistical test shows that there is correlation between physical condition of house with malaria recurrence (p = 0,009) and there is no correlation of behavior with malaria recurrence (p = 0,691).It is hoped that health workers will provide health information to the community through activities such as hygiene contest for each RT, in preventing malaria